GAMBARAN TINGKAT PENGETAHUAN PETUGAS DAN PENGUNJUNG KOLAM RENANG TENTANG PERTOLONGAN PERTAMA PADA KASUS TENGGELAM DI KOTA DENPASAR - Kesek, Bella Jenifer Rachael Maria; Saputra, I Kadek; Krisnawati, Komang Menik Sri (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023DO - 10.24843/coping.2023.v11.i06.p11, 2024)
Drowning is an accident that was caused by inadvertency or due to other factors such as lack of swimming skills and lack of warming up. This research will be conducted using quantitative methods with observational descriptive analytics. In this research, 63 participants were used by officers and visitors to the swimming pool (23 officers and 40 visitors to the swimming pool) using a proportional random sampling technique and total sampling and data collection was carried out using the Google form. The research results show that most of swimming pool officers and visitors have a good knowledge. Recommendation in this study is that any information related to first aid for drowning must be further developed with the aim of adding more knowledge and the latest information regarding drowning aid.